(untitled) (XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2020)
The combination of fashion and transformation frames a current reality where the subjects and their dressing practices are the objects of processes of a constantly mutating identity building. At the centre of the debate on fashion design there is always a human body which interacts and coexists with the technologies that inhabit it: they, at the same time, amplify the range of forms and operational possibilities based on the most advanced representation methods and prototyping of clothing and accessories, relating to innovative materials. The paper reflects on the modes of construction of the artefacts and on the methods of planar development of patterns, needful for the making of clothes and accessories, and at the same time investigates the inspiring principles of projects that relate with wefts traced directly on real bodies, or on their digital clones. The main case studies here presented concern the work of fashion designers and creative directors who experiment with digital technologies during the ideation, design, pattern making and prototyping phases, up to the visual communication of fashion garments and accessories. A complex kaleidoscope of free forms that fit moving bodies, in patterns and geometries that merge with the physicality of the subjects, and sometimes deny it, demonstrates that representation, in all its knowledge, is crucial in the fashion industry.